Methodological Opportunism in Management: The Use of the Case Study Method to Develop a New Construct Called IODD - Bachta, Anis; Maaref, Abdenasser; Debabi, Mohsen (Journal of Cultural Analysis and Social Change, 2025)
The different visions that organizational reality conveys generates a diversity of research methods allowing it to be approached from different perspectives. Such diversity of paths to reality in organizations often poses epistemological problems. In fact, by migrating from one vision of the organization to another we go through a continuum from subjective to objective and the methods of investigation change accordingly. In management sciences, this epistemological opposition between the positivist perspective and the constructivist one results in two research directions. Research traditions in management sciences generally mean that confirmatory research relies on quantitative techniques and exploratory research tends to adopt qualitative methods. However, can we really speak about antagonism between positivism and constructivism in management science? If not, what are the epistemological foundations of the case study as a research strategy in management sciences? Such a response marks, in our opinion, the need to adjust research paradigms by putting an end to the opposition between positivist positioning and constructivist positioning. Especially since such an opposition has been falsified since Piaget (1970) then by Latour (1991).